Peace Economics, Peace Science and Public Policy (De Gruyter, 1993)
The main objectives of Peace Economics, Peace Science and Public Policy are to further research in Peace Science and Peace Economics, to expose the scholarly community to innovative peace-related research, to disseminate the study of peace economics to a wider audience.